Моделювання передавача SOQPSK-TG сигналів - Янкевич, Р. В.; Мартюгов, С. О.; Токарчук, П. А.; Міськів, М. В.; Огородник, А. В. (Видавництво Львівської політехніки, 2013)
This paper is devoted to the practical side of the SOQPSK transmitter realization. It describes detailed model of one of possible variants of transmitter realization. The model is made in such a way that any part of it can be easily changed or any parameter can be tuned to achieve best efficiency of the system. The biggest problem to be solved when realizing transmitter is practical realization of ternary encoder. This paper also presents our solution of this problem using elemental discrete blocks that could be easily realized in practice either using discrete elements or included as part of system realized on FPGA. The paper itself is divided on four sections: 1. Introduction. This part contains the information about the development of telemetry systems, standard types of modulations and references links to the papers devoted to the problems of telemetry signals. 2. SOQPSK modulation and its kinds. This section contains theoretical statements and formulas of the SOQPSK type modulation. Also different parameters that define types of SOPQSK modulation (SOQPSK-A, SOQPSK-B, SOQPSK-TG) are presented. 3. Transmitter model. In this section the problem of telemetry SOQPSK-TG transmitter modeling is described. Next the step by step explanation of the model, its blocks and their operation is shown. Explanation is organized in the way how the input signal propagates from input to output. Also the problem of transmitter filter is described. Two possible solutions of this issue are shown in this section too. 4. Conclusions. Some short conclusions to this paper are given in this section. In general we can say that the necessity of new telemetry systems creation force the search for new, more effective modulations. Created standards describe some of the signals types and their parameters. But these stands do not fully describe methods of these signals generation. Within the work on creation of detailed model of SOQPSK transmitter the scheme of binary sequences of {-1, +1} alphabet to ternary sequences of {-1, 0, +1} alphabet was created. The created model allows to investigate the influence of its separate blocks’ parameters change on the whole system, but also easily make these changes. Also, it is necessary to point out that such model detail allows to make relatively easy practical realization just by transferring it to FPGA, which in now a days have big enough library of standard blocks and systems. Описано процес моделювання, а також результати моделювання передавального пристрою SOQPSK-TG сигналів. Представлено реалізацію двійково-трійкового перетворювача.
Modelling of transmitter of SOQPSK-TG signals
Keywords: telemetry; SOQPSK signals; ternary converters; телеметрія; SOQPSK сигнали; трійкові перетворювачі